2020
DOI: 10.1007/s42452-020-2445-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of thermal stratification and heat generation/absorption on MHD carreau nano fluid flow over a permeable cylinder

Abstract: The impact of magnetic field, nanoparticles on the two-dimensional flow of a generalized non-Newtonian Carreau fluid flow over a permeable cylindrical surface with no slip condition has been investigated in the existence of heat generation/absorption, thermal stratification and thermal radiation. The mentioned sets of nonlinear governing differential equations are converted into nonlinear ordinary differential equations by using appropriate similarity transformations and solved numerically and fiend with shoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Gopal et al [27] observed Brownian and thermophoresis effects on Casson nanofluid over a chemically reacting stretching sheet with an inclined magnetic field. A non-uniform heat generation or absorption of a stagnation point flow of nanofluid over an exponentially stretching sheet was discussed by Malvandi et al Gopal et al [36] employed the Runge-Kutta method for different geometrical models and resulted in numerically using MATLAB software. Sivaraj [37] analyzed the heat and mass transfer characteristics of cross nanofluid in stagnation point flow over a permeable extending or contracting surface.…”
Section: Numerical Modelmentioning
confidence: 99%
“…Gopal et al [27] observed Brownian and thermophoresis effects on Casson nanofluid over a chemically reacting stretching sheet with an inclined magnetic field. A non-uniform heat generation or absorption of a stagnation point flow of nanofluid over an exponentially stretching sheet was discussed by Malvandi et al Gopal et al [36] employed the Runge-Kutta method for different geometrical models and resulted in numerically using MATLAB software. Sivaraj [37] analyzed the heat and mass transfer characteristics of cross nanofluid in stagnation point flow over a permeable extending or contracting surface.…”
Section: Numerical Modelmentioning
confidence: 99%
“…The obtained results have been astonishing, encouraging researchers to explore these new kinds of fluids more extensively. The industrial importance of hybrid nanofluids is unimaginable, as hybrid nanofluids enhance heat transfer rates, reduce skin friction, and reduce production costs [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Madhu et al 9 reconnoitered the second law performance and entropy generation in the flow of Carreau fluid due to an inclined microchannel in the presence of the radiative heated convective condition. Analysis of magnetohydrodynamic (MHD) boundary layer flow of Carreau fluid pattern by a stretched permeable sheet due to both of the dependence of viscosity and thermal conductivity on the temperature has been executed by Abbas et al 10 Gopal et al 11 introduced a solution for the influence of the magnetic field, heat generation/absorption, thermal radiation, and thermal stratification on the flow of Carreau nanofluid over the surface of a permeable stretched cylinder.…”
Section: Introductionmentioning
confidence: 99%